Development of a mini-tribometer for in-situ observation of subsurface and the corresponding experiments. Issue 5 (13th July 2021) - Li, Chen; Wen, Heng; Chen, Kun; Zhang, Longxiao; Xie, Ting; Shi, Yaru; Zhang, Junlong
Abstract : Purpose: This paper aims to develop a Mini-Tribometer for in-situ observation of subsurface. Design/methodology/approach: To observe the change of the microstructure during wear in real time, an in-situ observation mini-tribometer was developed according to the requirements of the basic frictional experiments and carried out the verification experiments. Findings: The subsurface images and the tribological data obtained from the mini-tribometer clearly show that the graphite in the matrix moves to the surface and takes part in lubrication mainly in the form of extrusion and peeling off, and the migration of graphite in the copper-based composite to the frictional interface to act as lubricant and to result in the decrease of the friction coefficient. The experimental results of the developed tribometer are accurate, which can provide important references for further research on the wear mechanism of materials. Originality/value: The developed in-situ observation mini-tribometer can be used to observe the dynamic wear mechanism of the frictional pairs, which is very important for optimization of material design and tribological performances.